2009
DOI: 10.1073/pnas.0904069106
|View full text |Cite
|
Sign up to set email alerts
|

Heterodimeric geranyl(geranyl)diphosphate synthase from hop ( Humulus lupulus ) and the evolution of monoterpene biosynthesis

Abstract: Myrcene, which accounts for 30 -50% of the essential oil in hop (Humulus lupulus L.) trichomes, derives from geranyl diphosphate (GPP), the common precursor of monoterpenes. Full-length sequences of heterodimeric GPP synthase small subunit (GPPS.SSU, belonging to the SSU I subfamily) and large subunit (LSU) cDNAs were mined from a hop trichome cDNA library. The SSU was inactive, whereas the LSU produced GPP, farnesyl diphosphate, and geranylgeranyl diphosphate (GGPP) from dimethylallyl diphosphate and isopente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
246
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(261 citation statements)
references
References 34 publications
13
246
0
2
Order By: Relevance
“…In tobacco plants overexpressing three monoterpene synthases (CaMV35S promoter), the total level of additional monoterpenes emitted from leaves reached up to 30 ng h Ϫ1 g Ϫ1 FW (37), and plants overexpressing patchoulol synthase emitted patchoulol at levels of 50 -100 ng h Ϫ1 g Ϫ1 FW (6). The high efficiency of chrysanthemol production in plants suggests the possible presence of an endogenous phosphatase that efficiently hydrolyzes CPP or the presence of an endogenous cofactor that potentiates CDS activity (38,39). Our experiments and existing literature seem to best support the latter possibility for the reasons given below.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In tobacco plants overexpressing three monoterpene synthases (CaMV35S promoter), the total level of additional monoterpenes emitted from leaves reached up to 30 ng h Ϫ1 g Ϫ1 FW (37), and plants overexpressing patchoulol synthase emitted patchoulol at levels of 50 -100 ng h Ϫ1 g Ϫ1 FW (6). The high efficiency of chrysanthemol production in plants suggests the possible presence of an endogenous phosphatase that efficiently hydrolyzes CPP or the presence of an endogenous cofactor that potentiates CDS activity (38,39). Our experiments and existing literature seem to best support the latter possibility for the reasons given below.…”
Section: Discussionsupporting
confidence: 60%
“…13), can be estimated to be around 30 M, assuming a regression coefficient of 1 g ml Ϫ1 for leaf fresh weight to leaf volume (44), a chloroplast volume of 20% of total cell volume in mature leaf cells (45), and 60% of DMAPP to be found in the chloroplast (46). Third, inactive GDSs have been shown before to be activated by the formation of a heterodimer with geranylgeranyldiphospate synthase (39,47,48). The small subunits are usually inactive in the in vitro assays, and the big subunits are either inactive (35,49) or function as well as homodimeric geranylgeranyl diphosphate synthases (39,47,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of this subfamily are catalytically inactive but are able to bind GGPPS and modulate its product specificity from GGPP to GPP (11). Recombinant Os02g44780 protein (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the SSU II subfamily is present in both angiosperms and gymnosperms, to date, only one member of this subfamily was functionally characterized (11). It has been shown that Arabidopsis SSU II, although forming heterodimers with GGPPS, modifies the product profile and promotes the GPPS activity of GGPPS (11).…”
Section: Discussionmentioning
confidence: 99%